Odpowiedzi

2010-03-28T21:22:41+02:00
A) x + 12 = 4
x=4-12
x=-8

b) 27 - x =35
-x=35-27
-x=8 *(-1)
x=-8

c) 18 + x = -7
x=-7-18
x=-25

d) x - 16 = -9
x=-9+16
x=7

e) 81 - x = -13
-x=-13-81
-x=-94
x=94

f) - 19 + x =20
x=20+19
x=39

g) 8x = 3 / :8
x=3/8

h) 3/4x = -2
x=8/3
x=2⅔

i) - 0,6x = 9
x=90/6
x=15

1 5 1
2010-03-28T21:23:20+02:00
A) x = 4-12
x=-8
b)27-35 = x
x = -8
c)x=-7 - 18
x= -25
d) x = -9 +16
x= 7
e) x = -13 - 81
x = -94
f)x = 20+19
x = 39
g) 8x = 3 \ : 8
x = 3\8
h) 3\4x = -2 \ : 3\4
x = 2,66666667
i) - 0,6x = 9 \ : (- 0,6)
x = -15
1 5 1